Capitalism, religion, and the idea of the demonic - Christoph Deutschmann (Max Planck Institute for the Study of Societies, 2012)
Following the debate on the relationship between capitalism and religion, this paper discusses the role of religion in present-day capitalism. It argues that neither the secularization thesis nor the influential concepts of a 'return' or a 'transformation' of religions can offer a convincing interpretation of the challenges religions are faced with in modern capitalism. Partially following Habermas, the paper outlines an interactionist reinterpretation of Durkheim's theory of religion. It shows that from the viewpoint of such an interpretation, it is possible that the place of religion in modern societies can be filled not only by manifestly religious systems of meaning, but also by nominally nonreligious ones. I argue that the capital form of money can, in fact, assume the function of such a 'latent' religion in an apparently 'secularized' world. Nevertheless, to simply equate capitalism with religion, as many authors have suggested, would be shortsighted. Rather, as a characterization of the contemporary relationship between capitalism and religion, Paul Tillich's concept of the 'demonic' appears more promising. – – Anknüpfend an die Debatte über das Verhältnis von Kapitalismus und Religion bemüht sich der Beitrag um eine Klärung der Rolle der Religionen im gegenwärtigen Kapitalismus. Weder die in der Soziologie entwickelten Theorien der Säkularisierung und Modernisierung noch die gegenwärtig einflussreichen Thesen einer religiösen 'Wende' oder 'Transformation' können den Herausforderungen, mit denen die Religionen im gegenwärtigen Kapitalismus konfrontiert sind, wirklich gerecht werden. Der Beitrag skizziert, teilweise an Habermas anknüpfend, eine interaktionstheoretische Reformulierung von Durkheims Religionstheorie. Aus dieser Reformulierung ergibt sich die These, dass der Platz der Religion in modernen Gesellschaften auch durch nominell nicht religiöse Sinnsysteme eingenommen werden kann. Die Kapitalform des Geldes kann, wie dann gezeigt wird, die Funktion einer solchen 'latenten' Religion in einer vermeintlich 'säkularisierten' Welt einnehmen. Es wäre gleichwohl verkürzt, Kapitalismus und Religion einfach gleichzusetzen, wie eine Reihe Autoren es vorgeschlagen haben. Vielmehr bietet Paul Tillichs Theorie des 'Dämonischen' eine überzeugendere Konzeptualisierung des gegenwärtigen Verhältnisses von Kapitalismus und Religion.
Keywords: 300; Religion; Kapitalismus; Soziologie